Poems - Shakespeare, William, (The nonesuch press, 1953)
Conteúdo: Venus and Adonis.- The rape of Lucrece.- The sonnets.- A lovers complaint.- The passionate pilgrime.- Sonnets to sundry notes of Musicke.- The phoenix and turtle.